2007
DOI: 10.1016/j.seizure.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of 18F-FDG PET in preoperative epilepsy surgery evaluation for patients with temporal lobe epilepsy

Abstract: Our data confirm that ipsilateral PET hypometabolism may be an indicator for good postoperative outcome in presurgical evaluation of drug-resistant TLE, although the actual diagnostic added value remained questionable and unclear. PET does not appear to add value in patients localized by ictal scalp EEG and MRI. Prospective studies limited to non-localized ictal scalp EEG or MRI-negative patients are required for validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
108
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(120 citation statements)
references
References 58 publications
7
108
0
5
Order By: Relevance
“…Although the overall sensitivity of PET varied considerably across the studies, PET displayed moderate to high sensitivity in localizing the seizure focus among temporal lobe epilepsy patients (range, 71-89%). Again, this is in line with the previous meta-analysis which showed 86% of patients with good outcome had an ipsilateral PET finding (49). For MRI and EEG, the reported sensitivity (MRI 41-83%; EEG 36-81%) also varied greatly across the studies.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Although the overall sensitivity of PET varied considerably across the studies, PET displayed moderate to high sensitivity in localizing the seizure focus among temporal lobe epilepsy patients (range, 71-89%). Again, this is in line with the previous meta-analysis which showed 86% of patients with good outcome had an ipsilateral PET finding (49). For MRI and EEG, the reported sensitivity (MRI 41-83%; EEG 36-81%) also varied greatly across the studies.…”
supporting
confidence: 88%
“…A previous meta-analysis reported a concordance value of 67% between PET and invasive EEG recording. 49 This analysis included only patients with temporal lobe epilepsy and excluded pediatric patients. Still, data from this systematic review are consistent with their findings and showed a 56 to 90% agreement between PET hypometabolism and seizure onset localized by intracranial EEG among adults.…”
mentioning
confidence: 99%
“…La décharge ictale, sa voie de propagation ainsi que les remaniements structurels et la durée de l'épilepsie jouent un rôle dans ces résultats (25,26 (27). Les SPECT peuvent également être réalisées en phase interictale, mettant en évidence des hypoperfusions au niveau du ou des foyers épileptogènes.…”
Section: Sermentunclassified
“…The sensitivity of this procedure for detecting hypometabolism of the temporal lobe in the interictal state is high, ranging from 80 to 90% [2,3,7,9]. This method provides reliable information for lateralizing the epileptogenic temporal lobe in "MRI-negative" cases, with a yield ranging from 45 to almost 90 percent [2][3][4][5][6][7]. The sensitivity improves when seizures are frequent or when imaging is performed immediately after seizure onset [24].…”
Section: Imz-spect For Childhood Epilepsymentioning
confidence: 99%
“…However, some children with intractable focal epilepsy do not show any abnormal findings on brain MRI, and it is not always straightforward to identify the epileptic focus precisely based on clinical and EEG findings alone. In such cases, brain functional neuroimaging studies may be useful [2][3][4][5][6][7]. Many studies have reported the usefulness of interictal/ictal cerebral blood flow single photon emission computed tomography (SPECT) [8][9][10][11][12] and interictal 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) [2,3,7,10,13].…”
Section: Introductionmentioning
confidence: 99%